Ten Malaysians among world`s most influential scientific minds - Christina, Chin (The Star, 2017)
KUALA LUMPUR: Ten of the country's researchers are recognised as the world's most influential scientific minds of the year, says Higher Education Minister Datuk Seri Idris Jusoh.